Vascular Complications and Diabetes: Current Therapies and Future Challenges. (9th January 2012) - Willard, Abbott L.; Herman, Ira M.
Abstract : Diabetic retinal complications, including macular edema (DME) and proliferative diabetic retinopathy (PDR), are the leading cause of new cases of blindness among adults aged 20–74. Chronic hyperglycemia, considered the underlying cause of diabetic retinopathy, is thought to act first through violation of the pericyte-endothelial coupling. Disruption of microvascular integrity leads to pathologic consequences including hypoxia-induced imbalance in vascular endothelial growth factor (VEGF) signaling. Several anti-VEGF medications are in clinical trials for use in arresting retinal angiogenesis arising from DME and PDR. Although a review of current clinical trials shows promising results, the lack of large prospective studies, head-to-head therapeutic comparisons, and potential long-term and systemic adverse events give cause for optimistic caution. Alternative therapies including targeting pathogenic specific angiogenesis and mural-cell-based therapeutics may offer innovative solutions for currently intractable clinical problems. This paper describes the mechanisms behind diabetic retinal complications, current research supporting anti-VEGF medications, and future therapeutic directions.